2022
DOI: 10.1038/s41588-022-01208-7
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies rare damaging variants in ATP8B4 and ABCA1 as risk factors for Alzheimer’s disease

Abstract: Alzheimer’s disease (AD), the leading cause of dementia, has an estimated heritability of approximately 70%1. The genetic component of AD has been mainly assessed using genome-wide association studies, which do not capture the risk contributed by rare variants2. Here, we compared the gene-based burden of rare damaging variants in exome sequencing data from 32,558 individuals—16,036 AD cases and 16,522 controls. Next to variants in TREM2, SORL1 and ABCA7, we observed a significant association of rare, predicted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 34 publications
(45 reference statements)
1
68
0
Order By: Relevance
“…One individual with AD with age of onset in their 50s had a rare variant in ABCA7 (NM_019112.3:c.4010C>T, p.( Thr117Ile)) (returned as a VUS) that has not been identified in gnomAD or published to our knowledge. Rare missense variants in ABCA7 have been previously reported to have an odds ratio of 1.6 and loss-of-function variants have an odds ratio of 2.2 for individuals with EOAD (Holstege et al 2021). This individual met the missense criteria (allele frequency <1% and 'moderate' or 'high' variant effect predictor impact classification) described by Holstege, et al We predict this rare variant to be damaging due to its CADD score (23.9) and computational evidence supporting its deleterious effect on the gene or gene product.…”
Section: Rare Variants Of Uncertain Significancementioning
confidence: 99%
“…One individual with AD with age of onset in their 50s had a rare variant in ABCA7 (NM_019112.3:c.4010C>T, p.( Thr117Ile)) (returned as a VUS) that has not been identified in gnomAD or published to our knowledge. Rare missense variants in ABCA7 have been previously reported to have an odds ratio of 1.6 and loss-of-function variants have an odds ratio of 2.2 for individuals with EOAD (Holstege et al 2021). This individual met the missense criteria (allele frequency <1% and 'moderate' or 'high' variant effect predictor impact classification) described by Holstege, et al We predict this rare variant to be damaging due to its CADD score (23.9) and computational evidence supporting its deleterious effect on the gene or gene product.…”
Section: Rare Variants Of Uncertain Significancementioning
confidence: 99%
“…In the context of the international European Alzheimer & Dementia Biobank collaboration, we conducted the largest genome‐wide analysis of CSF biomarkers to date and found that in addition to apolipoprotein E, also CR1 was associated with an increased risk of reduced Aβ1‐42, and BIN1 was associated with an increased risk of elevated CSF tau. A second paper based on the largest whole‐exome sequencing analysis in AD to date (task 1.4) identified two novel variants in ATP8B4 and ABCA1 associated with AD risk, and a suggestive signal in ADAM10 , next to known variants in TREM2 , SORL1 , and ABCA7 21 . These results provide additional evidence for a major role for Aβ precursor protein processing, Aβ aggregation, lipid metabolism, and microglial function in AD.…”
Section: Current State Of Aboardmentioning
confidence: 86%
“…Therefore, the LXR / ABCA1 axis and ABCA transporters have been previously suggested as promising therapeutical targets in AD [ 50 , 51 , 52 , 53 ]. Recent identification of ABCA1 as an important genetic factor for AD by genome wide association studies (GWAS) strengthen this hypothesis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that ABCA1 -mediated cholesterol efflux is impaired in patients with AD and mild cognitive impairment [ 13 ]. More recently, genome-wide association studies (GWAS) have identified ABCA1 polymorphisms as strongly linked to a high risk of developing AD [ 14 ], thus reinforcing the hypothesis that the LXR / ABCA1 axis could be a promising drug target for AD. Despite these findings, the role of the LXR / ABCA1 axis in the CNS remains to be clarified, in particular for CNS cholesterol homeostasis.…”
Section: Introductionmentioning
confidence: 99%